Prof. Vlado Jurgučio įžvalgų apie pinigus analizė ir jų plėtotė lietuvių autorių darbuose - Giriūnas, Lukas; Mackevičius, Jonas (Buhalterinės apskaitos teorija ir praktika, 2014)
It should be noted that the name of professor V. Jurgutis was written into history for the long year’s research activities – he was one of the most distinguished Lithuanian financiers. Professor submitted interesting opinion about the money, its stability and circulation in his main scientific works: “The essence of the science of finance” (1938), “The money” (1938) and “Banks” (1940). It should be mentioned that the theories about money circulation and its management is very important because he had possibility to implement his theoretical ideas into practice. Analysis of Vladas Jurgutis researches showed that the aim of public finance management is to guarantee the stability of state finance, whereas managing state finance a  significantly  broader  goal  appears  –  to  guarantee “the nation’s welfare”, which includes: stability  of  the  financial  system  of  the  residents; stability of the companies’ finance and balancing of the public finance. Several Lithuanian economists have written papers on the issues of monetary policy and theory. Mainly they were the supporters of banking theory and were praising the stability of the currency parity.
Keywords: pinigai; pinigų funkcijos; pinigų vertė; pinigų infliacija; pinigų politika